Evolution of the legal frame of concession contracts and public-private partnerships in Peru - Nalvarte Salvatierra, Pierre (2017)
The present paper discusses the evolution of the legal frame of public-private partnership in Peru, putting accent in the incentives given to private investment made by these specific laws. For that purpose, the paper makes a meticulous analysis about the progressive inclusion made on the matter. Finally, a practical case is presented.